A novel approach for occupational health and safety and environment risk assessment for nuclear power plant construction project. (10th June 2020) - Sui, Yang; Ding, Rui; Wang, Hanqing
Abstract: Nuclear Power Plant (NPP) construction project is a mega one with high level of occupational health and safety and environment (OHSE) risks, and it is necessary to propose an approach for the OHSE risk assessment so as to prevent the OHSE accidents or reduce their outcomes. However, there has not been such an approach due to the high uncertainty and complexity of NPP construction project. Therefore, this paper proposed a novel approach for the OHSE risk assessment which includes systematically identifying the OHSE risks by using brainstorming method, establishing an OHSE risk assessment index system by using Delphi method, and formulating a mathematical model by combining set pair analysis (SPA), trapezoidal fuzzy number (TPFN), and set-valued statistics (SVS) methods for determining the overall OHSE risk level for NPP construction project. The approach was used to assess the OHSE risks for the NPP construction project in East China, and its overall OHSE risk level was assessed at level 2 (low OHSE risk level). In addition, the problems in the OHSE risk management were found, and the corresponding OHSE risk treatments for these problems were implemented. The results showed that the approach helped reduce the OHSE risk level and protect the workers' occupational health and safety and the environment while the NPP construction project was under construction. Highlights: A novel approach for OHSE risk assessment for NPP construction project. The OHSE risks for NPP construction project. The OHSE risk assessment index system for NPP construction project. A mathematical model for OHSE risk assessment for NPP construction project. The overall OHSE risk level for the NPP construction project in FQNP.